Blockchain-Enabled Telehealth Services Using Smart Contracts - Hasan, Haya R.; Salah, Khaled; Jayaraman, Raja; Yaqoob, Ibrar; Omar, Mohammed; Ellahham, Samer (IEEE access, 2021)
Telehealth has gained a huge traction during the Coronavirus (COVID-19) pandemic. Telehealth enables physicians and medical care providers to remotely care for patients and monitor their symptoms. Today's telehealth systems fall short in providing transparent, immutable, traceable, auditable, secure, and trustworthy services. In addition, they are centralized and subject to the single point of control and failure. In this paper, we propose a private blockchain-based solution to overcome the aforementioned challenges. We demonstrate how specifically three important telehealth services; namely, teleconsultation, drug administration, and medical testing can be enhanced using blockchain technology. Our proposed solution also ensures integrity, immutability, accountability, and non-repudiation for telehealth transactions initiated by multiple actors. For storing and keeping track of large-size digital content, such as images and audio and video recordings of telehealth service sessions, our proposed solution is integrated with off-chain storage systems including cloud storage or a decentralized storage system as that of the Interplanetary File System (IPFS). The registered participants are provided with access privileges based on their roles to ensure that restrictions are enforced on-chain. Smart contracts are developed to maintain data provenance and generate reliable alerts and notifications. The implementation and testing details of the algorithms are presented. We discuss, compare, and analyze the security features of our solution.